Pengelolaan Keuangan Koperasi Produsen Aneka Sulaman Kabupaten Agam - Menik Kurnia Siwi; Tri Kurniawati; Jean Elikal Marna (Jurnal Ecogen, 2020)
The development of cooperative business activities requires professional management of cooperatives, especially in the aspects of financial management. As a company, cooperatives certainly need good financial management so that cooperative business activities can run well. The limited knowledge of cooperative management on accounting knowledge, results in financial reporting that is not well structured and non-standardized, making it difficult for cooperatives to maintain and improve their capital. Koperasi Produsen Aneka Sulaman Agam regency is a cooperative that participates in government programs to develop Regional Superior Products with the One Village One Product (OVOP) Approach, therefore it requires reliable management. With this training activity, it is expected that the knowledge and abilities of cooperative management, especially in the management of cooperative finance, can be increased.Keywords : cooperative management, financial management